Social profit optimization with demand response management in electricity market: a multi-timescale leader-following approach - Wang, Jianzheng (2022)
In the electricity market, it is quite common that the market participants make ``selfish'' strategies to harvest the maximum profits for themselves, which may cause the social benefit loss and impair the sustainability of the market in the long term. Regarding this issue, we will study how the social profit can be improved through strategic demand response management. Specifically, we explore two interaction mechanisms in the market: Nash game and Stackelberg game. At the user side, each user makes the respective energy-purchasing strategy to optimize its own profit. At the utility company (UC) side, we consider multiple self-centric UCs that play games. A social-centric governmental UC is established as the leader to optimize the social profit of the market through competition. Then, a multi-timescale leader-following problem of the UCs is formulated under the coordination of an independent system operator. By our proposed demand function amelioration strategy, the market efficiency is maximized. In addition, by considering some additional constraints of the market, two projection-based algorithms are proposed. The feasibility of the proposed algorithms is verified with an IEEE 9-bus system model in the simulation.